Gradual vs entire sponsorship termination: How to manage the ending of a sponsorship engagement. Issue 4 (5th November 2018) - Dick, Christopher
Abstract : Purpose: The few studies on the effects of a sponsorship termination do not consider the effects of different exit options on consumers' attitudes toward the exiting sponsor. To fill this gap, the purpose of this paper is to investigate the effects of the extent of the exit (gradual vs entire) as well as the timing of the announcement (early vs late) on consumers' attitudes. Moreover, this research considers the mediating role of the perceived abandonment of the sponsored party. Design/methodology/approach: This research uses an experimental study ( n =204). Data were collected among supporters of a German second division soccer team. Findings: The results emphasize that the extent of the exit as well as the timing of the announcement influences consumers' attitudes. They develop negative attitudes toward the withdrawing sponsor, especially when the sponsor exits entirely instead of gradually and announces the decision late instead of early. Furthermore, the results reveal that the perceived abandonment of the sponsored party mediates the effect of the extent of exit on attitudes. Practical implications: The results help to formulate several exit options for the withdrawing sponsor that will help to minimize the possible negative effects on their brand. Specifically, the author recommends a gradual exit as well as an early announcement of the decision to prevent negative effects on the sponsor brand. Originality/value: This study expands the research on the effects of a sponsorship termination on consumers' attitudes toward the sponsor brand. Specifically, it is the first study that considers several aspects regarding the sponsor management of a sponsorship termination as important determinants of consumers' attitudes.